Establishing the effects of mesoporous silica nanoparticle properties on in vivo disposition using imaging-based pharmacokinetics - Prashant Dogra (Nature Portfolio, 2018)
Nanoparticle applications are limited by insufficient understanding of physiochemical properties on in vivo disposition. Here, the authors explore the influence of size, surface chemistry and administration on the biodisposition of mesoporous silica nanoparticles using image-based pharmacokinetics.